Long-Term Use of Statins Lowering the Risk of Rehospitalization Caused by Ischemic Stroke Among Middle-Aged Hyperlipidemic Patients: A Population-Based Study - Yin, Jiu-Haw; Peng, Giia-Sheun; Chen, Kang-Hua; Chu, Chi-Ming; Chien, Wu-Chien; Kao, Li-Ting; Wu, Chia-Chao; Yang, Chih-Wei; Tsai, Wen-Chiuan; Lin, Wei-Zhi; Wu, Yi-Syuan; Lin, Hung-Che; et al. (Frontiers in Pharmacology, 2021)
Background: The long-term effects of statin use on rehospitalization due to ischemic stroke (reHospIS) in hyperlipidemic patients are still unknown. Therefore, we aimed to assess the long-term risks of reHospIS for hyperlipidemic patients who were taking statins and non-statin lipid-lowering medicines on a regular basis. Methods and Materials: The National Health Insurance Research Database in Taiwan was used to conduct a 6-year cohort study of patients >45 years old (n = 9,098) who were newly diagnosed with hyperlipidemia and hospitalized for the first or second time due to IS. The risk of reHospIS was assessed using Cox proportional hazards regression model. Results: Non-statin lipid-lowering medicines regular users were associated with higher risk of reHospIS compared to stains users (hazard ratio, HR = 1.29–1.39, p < 0.05). Rosuvastatin was the most preferred lipid-lowering medicine with lower HRs of reHospIS in hyperlipidemic patients whether they developed diabetes or not. Bezafibrate regular users of hyperlipidemic patients developing diabetes (HR = 2.15, p < 0.01) had nearly 50% lower reHospIS risks than those without diabetes (HR = 4.27, p < 0.05). Age, gender, drug dosage, comorbidities of diabetes and heart failure, and characteristics of first hospitalization due to IS were all adjusted in models. Moreover, increasing trends of HRs of reHospIS were observed from Rosuvastatin, non-statin lipid-lowering medicines, Lovastatin, and Gemfibrozil to Bezafibrate users. Conclusions: Statins were associated with long-term secondary prevention of reHospIS for hyperlipidemic patients. Rosuvastatin seemed to have the best protective effects. On the other hand, Bezafibrate appears to be beneficial for hyperlipidemic patients developing diabetes. Further research into the combination treatment of statin and non-statin lipid-lowering medicines in hyperlipidemic patients developing diabetes is warranted.